DAMPAK VARIASI SUHU TERHADAP KEKUATAN DAMPAK, KEKERASAN DAN METALOGRAFI PADA BAJA ST 37 UNTUK PELAT PERLAKUAN PANAS DAN PEMADAMAN - Nurdin, Dwi Purwanto; Haris, Oscar; Julianto, Eko (Suara Teknik : Jurnal Ilmiah, 2024)
Heat treatment of ST37 steel which is heated from the 1st temperature of 300 ℃, the 2nd temperature of 500 ℃ to 900 ℃ results in a hardness value that is relatively increasing, by using a method of quenching with water rapidly. The hardness value that was obtained before heat treatment averaged 52.62 VHN while after the heat treatment of ST37 steel obtained a hardness value of 85.56 VHN, the results of the impact test on ST37 steel averaged 52.73 Joules, this indicates that heat treatment of ST37 steel can increase the mechanical characteristics of the material with heating up to 900 ℃.